Second Language Learners’ Awareness of Adjectivalisation: The Challenge of Differentiating between Verbal Participles and Adjectival Participles by Libyan EFL Students (The International Journal of Educational Sciences and Arts, 2024)
This study explores Libyan EFL learners’ awareness of the process of adjectivalisation, and more specifically the process of using the participle form and progressive form of verbs as adjectives used in English Language. In addition, this study aims to test Libyan students’ recognition of adjectival participles and whether they will be able to distinguish them from verbal participles, prove them as real adjectives with their progressive – ing, and participle – ed, – en forms, and find out appropriate Arabic equivalents of these adjectives easily. The data gathered for this study were based on students’ marks they got by answering a two-part test consisting of an introductory part which is a multiple-choice test, followed by the main part which is the translation test. In the first part, the participants who were 30 students enrolled in Translation III course, were asked to choose the correct adjectivalised participle, and in the second part, the participants were asked to translate some participles used as adjectives into Arabic language. The study was mainly based on quantitatively as well as qualitatively analysing students’ answers to the test questions. The findings of this research revealed that only 16.67 % of the participating students successfully recognized verbal participles used as adjectives. On the other hand, 33.33 % of the students have appropriately rendered the involved de-participle adjectives into Arabic. In addition to the previous results, 20 % of the respondents properly recognized the present participle adjectives, whereas 50% of them truly recognized past adjectival participles in English.
Keywords: Adjectivalisation; Past Participles; EFL Libyan Learners; Translation Tests